2018
DOI: 10.16925/pe.v14i24.2412
|View full text |Cite
|
Sign up to set email alerts
|

El Cuestionario Breve de Evitación Experiencial

Abstract: Introducción: La evitación experiencial (EE) es un concepto central para el estudio de la psicopatología desde una perspectiva contextual-conductual. El Cuestionario de Aceptación y Acción II (AAQ-II) se ha convertido en la medida más utilizada de EE. Sin embargo, algunos autores han cuestionado seriamente su validez. En este contexto, el Cuestionario Breve de Evitación Experiencial (BEAQ) constituye una alternativa prometedora. Objetivo: El presente estudio buscó traducir al español el BEAQ y analizar s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…A recent study attempted to develop a Spanish version of the BEAQ, but failed to replicate the one-dimensional structure of the original (Valencia, 2018). Instead, this study found two possible underlying dimensions of the BEAQ, only one of which seemed to be a clear, straightforward measure of EA.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…A recent study attempted to develop a Spanish version of the BEAQ, but failed to replicate the one-dimensional structure of the original (Valencia, 2018). Instead, this study found two possible underlying dimensions of the BEAQ, only one of which seemed to be a clear, straightforward measure of EA.…”
Section: Introductionmentioning
confidence: 90%
“…It was constructed by assembling items from the BEAQ (Gámez et al, 2014) and the AFQ-Y (Greco et al, 2008). First, five items from the BEAQ were selected based on Valencia's (2018) study, where a subset of items were identified as better indicators of EA. These items had been previously back-translated and revised by an expert panel.…”
Section: Itemmentioning
confidence: 99%
See 1 more Smart Citation
“…En la construcción de los primeros cuestionarios se siguió un método extenso que involucró a docenas de terapeutas e investigadores de gran experiencia en la práctica de intervenciones contextuales, especialmente en ACT (Hayes et al, 2006), quienes desarrollaron cientos de reactivos preliminares (Hayes et al, 2004a) que fueron validados y corregidos con base en estudios estadísticos (Bond et al, 2011). Esta robusta metodología explica que, no obstante otros esfuerzos por construir instrumentos nuevos para evaluar mejor o más ampliamente el constructo (Valencia, 2018), los instrumentos de la serie AAQ continúan siendo el punto de partida para el desarrollo de otras mediciones de la flexibilidad psicológica adaptadas a contextos específicos (Ong, Lee et al, 2019).…”
Section: Conceptualización Y Medición De La Flexibilidad Psicológica:...unclassified